2016
DOI: 10.1080/1528008x.2016.1230037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Technical and Functional Quality on Guests’ Perceived Hotel Service Quality and Satisfaction: A SEM-PLS Analysis

Abstract: Numerous models on perceived service quality are discussed in literature besides SERVQUAL including technical and functional quality model. Functional quality attributes have been well studied but studies about technical quality attributes are rather limited. This article aims to integrate existing frameworks and propose antecedents towards perceived service quality and resulting customer satisfaction. A total of 204 questionnaires were collected from the guests staying at hotels in Malaysia. Partial least squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 79 publications
(159 reference statements)
0
44
1
1
Order By: Relevance
“…Customer loyalty has become one of the pivotal strategic marketing tools for business survival and is a complex construct that includes a set of behaviors and attitudes (Hussein et al, 2018). The hospitality industry recognizes that superior quality of service is one of the important marketing factors in driving satisfaction (Chen, 2013; Ren et al, 2016; Sari et al, 2016), which has added value, and subsequently leads to customer loyalty (Ali et al, 2017; Kandampully and Hsin-Hui, 2007). This sees the mantra of excellent service extremely important in the hotel industry especially within the five-star ratings hotels.…”
Section: Introductionmentioning
confidence: 99%
“…Customer loyalty has become one of the pivotal strategic marketing tools for business survival and is a complex construct that includes a set of behaviors and attitudes (Hussein et al, 2018). The hospitality industry recognizes that superior quality of service is one of the important marketing factors in driving satisfaction (Chen, 2013; Ren et al, 2016; Sari et al, 2016), which has added value, and subsequently leads to customer loyalty (Ali et al, 2017; Kandampully and Hsin-Hui, 2007). This sees the mantra of excellent service extremely important in the hotel industry especially within the five-star ratings hotels.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ali et al (2017) and Lee and Cheng (2018), none of the proposed alternative models has yet been subjected to sufficient academic evaluation. Moreover, all new models are based on the concept of service quality gaps, as first suggested by Parasuraman, Zeithaml, and Berry (1988).…”
Section: Literature Review 1service Quality Measurementmentioning
confidence: 99%
“…For example, Lin et al (2009) upgraded the traditional Importance Performance Analysis (ipa) with service quality gap evaluation and developed a new instrument called ipga (Importance Performance Gap Analyses), Saeida Ardakani, Nejatian, Farhangnejad, and Nejati (2015) applied a fuzzy-logic method to service quality evaluation, while Kukanja et al (2017) developed a service quality model based on the concept of Kotler's marketing mix. According to Ali, Hussain, Konar, and Jeon (2017), none of these alternative models received significant academic validation. Moreover, Ali et al (2017) found that all alternative models were conceptually based on the gap model, as first proposed by Parasuraman et al (1985).…”
Section: Literature Review Service Qualitymentioning
confidence: 99%
“…According to Ali, Hussain, Konar, and Jeon (2017), none of these alternative models received significant academic validation. Moreover, Ali et al (2017) found that all alternative models were conceptually based on the gap model, as first proposed by Parasuraman et al (1985). This view was also supported by Sharif and Kassim (2012), who state that the predominant quantitative measurement technique in hospitality and tourism research remains the servqual instrument with all its modifications.…”
Section: Literature Review Service Qualitymentioning
confidence: 99%